Upconversion luminescent nanomaterials: A promising new platform for food safety analysis. Issue 32 (14th November 2022) - Abdul Hakeem, Deshmukh; Su, Shaoshan; Mo, Zhurong; Wen, Hongli
Abstract: Foodborne diseases have become a significant threat to public health worldwide. Development of analytical techniques that enable fast and accurate detection of foodborne pathogens is significant for food science and safety research. Assays based on lanthanide (Ln) ion-doped upconversion nanoparticles (UCNPs) show up as a cutting edge platform in biomedical fields because of the superior physicochemical features of UCNPs, including negligible autofluorescence, large signal-to-noise ratio, minimum photodamage to biological samples, high penetration depth, and attractive optical and chemical features. In recent decades, this novel and promising technology has been gradually introduced to food safety research. Herein, we have reviewed the recent progress of Ln 3+ -doped UCNPs in food safety research with emphasis on the following aspects: 1) the upconversion mechanism and detection principles; 2) the history of UCNPs development in analytical chemistry; 3) the in-depth state-of-the-art synthesis strategies, including synthesis protocols for UCNPs, luminescence, structure, morphology, and surface engineering; 4) applications of UCNPs in foodborne pathogens detection, including mycotoxins, heavy metal ions, pesticide residue, antibiotics, estrogen residue, and pathogenic bacteria; and 5) the challenging and future perspectives of using UCNPs in food safety research. Considering the diversity and complexity of the foodborne harmful substances, developing novel detections and quantification techniques and the rigorous investigations about the effect of the harmful substances on human health should be accelerated.